Prevalence of pneumonia and malnutrition among children in Jigawa state, Nigeria: a community-based clinical screening study - Hamish R Graham; Adegoke G Falade; Tim Colbourn; Eric D McCollum; Ayobami Adebayo Bakare; Adegoke Gbadegesin Falade; Carina King; Christine Cassar; Agnese Iuliano; Adamu Isah; Adams Osebi; Tahlil Ahmed; et al. (BMJ Publishing Group, 2022)
Objective To estimate the point prevalence of pneumonia and malnutrition and explore associations with household socioeconomic factors.Design Community-based cross-sectional study conducted in January-June 2021 among a random sample of households across all villages in the study area.Setting Kiyawa Local Government Area, Jigawa state, Nigeria.Participants Children aged 0-59 months who were permanent residents in Kiyawa and present at home at the time of the survey.Main outcome measures Pneumonia (non-severe and severe) defined using WHO criteria (2014 revision) in children aged 0-59 months. Malnutrition (moderate and severe) defined using mid-upper arm circumference in children aged 6-59 months.Results 9171 children were assessed, with a mean age of 24.8 months (SD=15.8); 48.7% were girls. Overall pneumonia (severe or non-severe) point prevalence was 1.3% (n=121/9171); 0.6% (n=55/9171) had severe pneumonia. Using an alternate definition that did not rely on caregiver-reported cough/difficult breathing revealed higher pneumonia prevalence (n=258, 2.8%, 0.6% severe, 2.2% non-severe). Access to any toilet facility was associated with lower odds of pneumonia (aOR: 0.56; 95% CI: 0.31 to 1.01). The prevalence of malnutrition (moderate or severe) was 15.6% (n=1239/7954) with 4.1% (n=329/7954) were severely malnourished. Being older (aOR: 0.22; 95% CI: 0.17 to 0.27), male (aOR: 0.77; 95% CI: 0.66 to 0.91) and having head of compound a business owner or professional (vs subsistence farmer, aOR 0.71; 95% CI: 0.56 to 0.90) were associated with lower odds of malnutrition.Conclusions In this large, representative community-based survey, there was a considerable pneumonia and malnutrition morbidity burden. We noted challenges in the diagnosis of Integrated Management of Childhood Illness-defined pneumonia in this context.